Study on Flow Characteristics and Heat Transfer Behavior Around Different Geometrical Corrugated Extended Surfaces - Mousa, Naseer Abdul Razzaq (Al-Khwarizmi Engineering Journal, 2015)
Abstract The current study presents numerical investigation of the fluid (air) flow characteristics and convection heat transfer around different corrugated surfaces geometry in the low Reynolds number region (Re<1000). The geometries are included wavy, triangle, and rectangular. The effect of different geometry parameters such as aspect ratio and number of cycles per unit length on flow field characteristics and heat transfer was estimated and compared with each other. The computerized fluid dynamics package (ANSYS 14) is used to simulate the flow field and heat transfer, solve the governing equations, and extract the results. It is found that the turbulence intensity for rectangular extended surface was larger than that of triangle and wavy extended surfaces at the same aspect ratio and number of cycles per unit length. Also, the increasing of turbulence intensity leads to enhance the heat transfer coefficient and consequently the amount of heat transfer. According to previous results, if the pressure head losses along the upstream are not important, the using of rectangular extended surface is better than the triangle which is also better than wavy extended surface. Keywords: Flow Characteristics, Heat Transfer, Corrugated Surfaces, Numerical Analysis by ANSYS.